Endoscopist’s Satisfaction with the Insertion Phase of Colonoscopy Is a Potential Quality Indicator for Colorectal Polyp Detection: A Propensity Score Matching Study - Fumiaki Ishibashi,; Fumiaki Ishibashi,; Sho Suzuki,; Kentaro Mochida,; Mizuki Nagai,; Konomi Kobayashi,; Tomohiro Kawakami,; Tetsuo Morishita, (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Quality indicators during the insertion phase of colonoscopy require exploration. Unsatisfactory insertion experiences cause endoscopist psychophysiological fatigue and affect the quality of their inspection. This comparative study used propensity score matching (PSM) to determine whether endoscopist satisfaction during scope insertion was related to polyp detection rate (PDR).Materials and Methods: Patients who underwent colonoscopy screening between April 2019 and December 2022 were enrolled in this study. The endoscopist satisfaction score (high and low) during the insertion phase in each examination was recorded based on the level of fatigue and presence of paradoxical scope movement. All examinations were classified into 2 groups: a high and a low satisfaction score group. After PSM with potential confounding factors related to polyp detection (endoscopist, insertion and withdrawal time, and sedative agent use), the PDR and adenoma detection rate (ADR) were compared.Results: Overall, 4142 patients (average age, 54.1 years old; 54.4% male) underwent colonoscopies performed by twelve experienced endoscopists. Analysis using a logistic regression model revealed that a high satisfaction score during the insertion phase was an independent predictor of polyp detection (P < .001, odds ratio 1.79, 95% CI 1.41-2.33), whereas insertion time was not. After PSM, 513 patients from both groups were eligible for comparison. Polyp detection rate and ADR were significantly higher in the high-satisfaction group than in the low-satisfaction group (49.5% vs. 36.6%, P < .001; 35.1% vs. 27.1%, P = .007).Conclusion: The endoscopists’ level of satisfaction with the insertion phase was shown to be a potential predictor of PDR in screening colonoscopy.Cite this article as: Ishibashi F, Suzuki S, Mochida K, et al. Endoscopist’s satisfaction with the insertion phase of colonoscopy is a potential quality indicator for colorectal polyp detection: A propensity score matching study. Turk J Gastroenterol. 2024;35(6):488-496